Associations between Helicobacter pylori with nonalcoholic fatty liver disease and other metabolic conditions in Guatemala. Issue 6 (2nd October 2020) - Alvarez, Christian S.; Florio, Andrea A.; Butt, Julia; Rivera‐Andrade, Alvaro; Kroker‐Lobos, María F.; Waterboer, Tim; Camargo, Maria Constanza; Freedman, Neal D.; Graubard, Barry I.; Lazo, Mariana; Guallar, Eliseo; Groopman, John D.; et al.
Abstract: Background: Previous studies have suggested an association between Helicobacter pylori ( H pylori ) and nonalcoholic fatty liver disease (NAFLD). The aim of the current study was to examine the association in Guatemala, a region with elevated prevalences of both H pylori and NAFLD. Associations between H pylori and other metabolic conditions were also examined, as were associations between H hepaticus and H bilis and the metabolic conditions. Materials & Methods: The analysis included 424 participants from a cross‐sectional study in Guatemala. H pylori seropositivity was defined as positivity for ≥ 4 antigens. Seropositivities for H bilis and H hepaticus were defined as positivity for ≥ 2 antigens. NAFLD was estimated using the Fatty Liver Index and the Hepatic Steatosis Index. Other conditions examined were obesity, central obesity, hypercholesterolemia, low HDL, diabetes and metabolic syndrome (MetSyn). Prevalence odds ratios (POR) and 95% confidence intervals (CIs) were estimated. Results: No overall associations between H pylori, H hepaticus, or H bilis and NAFLD or related metabolic conditions were found. Seropositivity for H pylori antigens CagA and VacA and H hepaticus antigen HH0713 was each significantly associated with NAFLD, however. In addition, associations were observed between the H pylori antigens HyuA, HP1564, and UreA and specified metabolic conditions. Conclusions: While no overall associations between H pylori or Helicobacter species with NAFLD or related conditions were observed, some selected Helicobacter spp. antigens were associated with NAFLD. Further research is warranted to examine whether H . species are associated with any metabolic condition.